ARTICLE SUMMARIES. (Computer (00189162), 2007)
The article comprises summaries of six articles in the May 1, 2007, issue of "Computer," including "A Communication Support System for Older People with Dementia," "Holistic Sensing and Active Displays for Intelligent Driver Support Systems," and "Caravela: A Novel Stream-Based Distributed Computing Environment."